Evaluation of drug candidature: In silico ADMET, binding interactions with CDK7 and normal cell line studies of potentially anti-breast cancer enamidines. (December 2019) - Bansode, Prakash; Anantacharya, R.; Dhanavade, Maruti; Kamble, Subodh; Barale, Sagar; Sonawane, Kailas; Satyanarayan, Nayak D.; Rashinkar, Gajanan
Graphical abstract: Highlights: In silico ADMET of novel series of potentially anti-breast cancerous enamidines. Good drug likeliness and bioactivity scores of synthesized enamidines. Molecular docking of four lead molecules 4a-c and 4h with CDK7. To develop better CDK7 inhibitors. Low toxicity on vero cells. Abstract: We have recently explored novel class of potentially anti-breast cancer active enamidines in which four molecules 4a-c and 4h showed higher anticancer activity compared to standard drug doxorubicin . As a part of extension of this work, we have further evaluated in silico cheminformatic studies on bioactivity prediction of synthesized series of enamidines using mole information. The normal cell line study of four lead compounds 4a-c and 4h against African green monkey kidney vero strain further revealed that the compounds complemented good selectivity in inhibition of cancer cells. The in silico bioactivity and molecular docking studies also revealed that the compounds have significant interactions with the drug targets. The results reveal that enamidine moieties are vital for anti-breast cancer activity as they possess excellent drug-like characteristics, being potentially good inhibitors of cyclin dependent kinases7 (CDK7).